Ocular Manifestations in Patients with Sensorineural Hearing Loss - Haniah A. Zaheer; Deepika C Parameswarappa; Myra A. Zaheer; Jay Chhablani; Preeti Patil-Chhablani (Journal of Ophthalmic & Vision Research, 2022)
Abstract Identification of ocular manifestations in patients with sensorineural hearing loss (SNHL) can have a large impact on the outcome and treatment of pediatric patients. Due to the common co-incidence of ocular manifestations and SNHL in children, both ophthalmologic and hearing loss screening and routine examinations must be conducted to minimize adverse outcomes and worsening of pathology. Early evaluation and diagnosis is imperative for intervention and further development of the patient. Co-incidence requires a thorough evaluation that includes a comprehensive history, examination, and diagnostic testing. In this article, a literature review was conducted to analyze the presentations of various diseases and syndromes, such as Alport Syndrome, Waardenburg Syndrome, Norrie Disease, Usher Disease, Stickler Syndrome, Marfan Syndrome, Congenital Rubella, and Hereditary Optic Neuropathies. We divided the various ocular pathologies into anterior and posterior segment presentations and associated systemic findings for better understanding. Additionally, this review aims to include an update on the management of patients with both ocular and hearing loss manifestations.